Liquid phase microextraction strategies and their application in the determination of endocrine disruptive compounds in food samples - Chormey, Dotse Selali; Zaman, Buse Tugba; Kasa, Nursu Aylin; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2020)
Advancement in technology has led to the development of highly sensitive, accurate, efficient and robust analytical instrumentals, but without sample preparation, these state-of-the-art instruments are not capable of analyzing samples. Liquid-liquid extraction (LLE) was a widely used sample preparation technique, but setbacks such as long extraction periods, consumption of toxic solvents in large amounts and low efficiency led to its miniaturization, which is commonly termed liquid phase microextraction (LPME). LPME methods such as single drop microextraction, dispersive liquid-liquid microextraction and solidified floating organic drop microextraction overcome the limitations of the conventional LLE, and recent researches have focused on greener microextraction strategies based on extractants like ionic liquids and switchable polarity solvents. This review is aimed at presenting readers with a comprehensive overview of liquid phase microextraction methods, recent developments and novel approaches that are used to extract/preconcentrate endocrine disruptive compounds from food matrices for instrumental analysis. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Liquid phase microextraction (LPME); Endocrine disruptive compounds (EDCs); Single drop microextraction (SDME); Dispersive liquid-liquid microextraction (DLLME); Solidified floating organic drop microextraction (SFODME); Hollow fiber liquid-phase microextraction (HF-LPME); Chromatography; SINGLE-DROP MICROEXTRACTION; CLOUD POINT EXTRACTION; ENHANCED EMULSIFICATION MICROEXTRACTION; MICROWAVE-ASSISTED EXTRACTION; ELECTRON CAPTURE DETECTION; FLOATING ORGANIC DROPLET; GAS-CHROMATOGRAPHY; ORGANOPHOSPHORUS PESTICIDES; SENSITIVE DETERMINATION; MASS-SPECTROMETRY; Chemistry